Adenocarcinoma of the prostate with endometrioid features - (:unkn) unknown (Kluwer Academic Publishers, 1991)
Two cases of prostatic carcinoma with papillary features resembling the so-called "endometrioid carcinoma" are presented. Immunohistochemical studies, response to therapy and review of the literature support the ductal origin of the tumour, probably multifocal, as it is commonly seen in conjunction with acinotubular carcinoma. © 1991 Akadémiai Kiadó.